Pengembangan Lembar Kerja Siswa Menggunakan Pendekatan Matematika Realistik Indonesia Materi Persamaan Linear Dua Variabel di Kelas VIII - Rani Refianti; Maria Luthfiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study's objective is to create reliable and useful student worksheets (LKS) that apply the PMRI method of realistic mathematics in Indonesia. Research and development (R&D) employing a 4-D development model, which includes the processes of defining, designing, developing, and deploying, is the research methodology employed in this study. Three specialists, including linguists, media experts, and material experts, were surveyed as part of the study's data collection method. To ascertain whether the produced LKS was valid, the questionnaire given to three experts was examined. Students in the small group and large group levels are given surveys to complete about the usefulness of worksheets. After that, the practicality questionnaire was examined to see how practical the worksheets under development were. The produced LKS is recognized to be valid based on the validity questionnaire analysis results, with an average score of 3.09 established based on the LKS assessment results from three expert experts (material experts, linguists, and media experts). Based on calculations made from the answers on a practicality questionnaire, worksheets have an average practicality score of 3.23. As a result, the developed LKS falls into the practical category and can be used. Keywords: Development, Practical, Valid.